Textile Wastewater Treatment by Electrocoagulation Method - Han, Bing; Song, Tie-Hong; Zhang, Kun; Wang, Xiao-Ling (Asian Journal of Chemistry, 2014)
Electrocoagulation method with iron and aluminum electrodes was used to treat textile wastewater, and the effects of initial pH value, current density, electrocoagulation time on the final pH value, the removal rate of COD, power consumption and electrodes loss were investigated. The results showed that under the condition of initial pH value 7, after electrocoagulation by iron and aluminum electrodes the final pH value increased but not more than 8. When the current density was 7.5 mA/cm2, COD removal rate of the iron electrodes could reach 72 %. When electrocoagulation time was 15 min COD removal rate of the iron electrodes could reach 76 % and the power consumption was lower than the aluminum electrodes. The optimal electrocoagulation conditions were as follows: iron electrodes were used, the initial pH value was neutral, the current density was 7.5 mA/cm2 and electrocoagulation time was 15 min.